The Effect of Leadership and Incentive on Employee’s Performance at Hamparan Perak District - Siswa Pratama; Rindi Andika; Suwarno Suwarno; Syahrul Ramadhani (International Forum of Researchers and Lecturers, 2024)
The purpose of this study was to investigate the partial and simultaneous effects of leadership and incentive on employee’s performance at Hamparan Perak district. The Likert scale approach was utilized to collect data for this study, which employed quantitative methodologies. Using complete sampling, 60 employees from the Hamparan Perak district served as the study's subjects. The study's findings showed that, first, leadership significantly and favorably affects employee performance, as seen by the tcount > ttable value of 6.534 > 1.764, a result value of 0.559, and a sig value of 0.005 < 0.05. Second, tcount > ttable, which is 6.859 ˃ 1.764 with a result value of 0.540 and a sig value of 0.002 < 0.05, indicates that incentive have a positive and substantial impact on employee’s performance. Third, the results of the fcount > ftable, which are 11.897 > 2.608 with a result value of 0.721 and Sig value < 0.05 then 0.004 > 0.05, were obtained concurrently with the F test, demonstrating that leadership and incentives have a significant and positive impact on employee’s performance at Hamparan Perak district.